2003
DOI: 10.1590/s0100-83582003000200018
|View full text |Cite
|
Sign up to set email alerts
|

Critérios para avaliação do potencial de lixiviação dos herbicidas comercializados no Estado do Paraná

Abstract: Foi realizado um levantamento referente à comercialização de herbicidas no Estado do Paraná, visando quantificar o volume de sua utilização durante o ano de 2000. Em seguida, com base nas propriedades químicas desses herbicidas, estudaram-se critérios teóricos para classificá-los de acordo com o potencial de lixiviação. A análise dos dados do levantamento indicou que o maior volume comercializado ocorreu no quarto trimestre, relacionando-se provavelmente ao aumento da demanda provocada pela safra de verão. Os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
59

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(103 citation statements)
references
References 32 publications
1
43
0
59
Order By: Relevance
“…The log Kow of S-metolachlor is 2.89, exhibiting moderate sorption to colloids in the soil and plant cover (Aslam et al 2015). However, sorption levels of S-metolachlor rise with the decomposition of plant cover, due to an increase in the external surface area for sorption of the herbicide (Iqbal et al 2013); 3) the product may have been absorbed by the leaves or roots of the live plant cover; 4) S-metolachlor may have leached to depths greater than 18 cm, since cumulative rainfall was high. In some cases, this herbicide was detected at depths of up to 1 m and at concentrations of 0.230 μg L -1 (Marín-Benito et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The log Kow of S-metolachlor is 2.89, exhibiting moderate sorption to colloids in the soil and plant cover (Aslam et al 2015). However, sorption levels of S-metolachlor rise with the decomposition of plant cover, due to an increase in the external surface area for sorption of the herbicide (Iqbal et al 2013); 3) the product may have been absorbed by the leaves or roots of the live plant cover; 4) S-metolachlor may have leached to depths greater than 18 cm, since cumulative rainfall was high. In some cases, this herbicide was detected at depths of up to 1 m and at concentrations of 0.230 μg L -1 (Marín-Benito et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, mathematical models demonstrate that metolachlor has leaching potential (Inoue et al 2003). Under field conditions, research has shown different levels of leaching for this herbicide.…”
Section: Abstract Resumomentioning
confidence: 99%
“…After they have been applied to agricultural areas, herbicides undergo transport processes between environmental sectors by leaching and surface runoff . By leaching, the downward movement of herbicides in the soil profile, molecules move to deeper layers with the potential to degrade groundwater, especially when soil is highly permeable and/or the water table is close to the surface (Inoue et al, 2003). Surface runoff, on the other hand, allows the transport of molecules adsorbed on sediments or in solution, leading to degradation of surface waters .…”
Section: Introductionmentioning
confidence: 99%
“…Todavia, herbicidas que apresentam longo efeito residual em solos -muito utilizados no Brasil em pastagens e em diversas culturas agrícolas -podem causar sérios problemas ambientais, como a contaminação do solo, da água e da microbiota do solo (Inoue et al, 2003). Desse modo, estudos sobre sorção, dessorção, meia-vida e lixiviação de herbicidas no perfil do solo são necessários para se prever a eficá-cia do controle das plantas daninhas, o risco de prejuízo a culturas sensíveis plantadas em sequência, bem como o potencial de o herbicida atingir aquíferos subterrâneos (van Wyk & Reinhardt, 2001).…”
Section: Introductionunclassified
“…Devido à necessidade de uso racional dos insumos agrícolas para minimizar os impactos ambientais da agricultura, muitos estudos têm sido realizados com o objetivo de compreender o comportamento de herbicidas no solo (Futch et al, 1999;Pang et al, 2000;Carrizosa et al, 2004). No entanto, pouco se sabe a Lixiviação do picloram em Argissolo Vermelho-Amarelo e ... respeito do comportamento desses xenobió-ticos em solos tropicais (Inoue, 2002(Inoue, , 2003. Portanto, estudos dos solos tropicais, envolvendo características como a presença de cargas dependentes de pH, minerais de argila 1:1 (óxidos de ferro e alumínio), matéria orgâ-nica e a CTC total e o destino dos herbicidas no ambiente, necessitam ser implementados.…”
Section: Introductionunclassified